Effect of pruning and polyethylene bags in the conservation of cassava roots during storage - Paranaíba, José Luiz Vilela; Chagas, Silvio Júlio de Resende; Costa, Laerte (Pesquisa Agropecuaria Brasileira, 1996)
The effect of priming and of the use of polyethylene bags during storage of cassava (Manihot esculenta Crantz) on the physiological decay, vitamin C, and moisture content was verified. Pruning was performed 16 months after planting, and roots were harvested after 0, 7, 14, 21 and 28 days. Roots were later packed in polyethylene bags. Pruning, as well as use of bags, induced physiological decay and reduction of total vitamin C contents. The moisture content was not affected by pruning but was higher in packed roots.